Regiospecificity of Dioxygenation of Di- to Pentachlorobiphenyls and Their Degradation to Chlorobenzoates by the bph-Encoded Catabolic Pathway of Burkholderia sp. Strain LB400 - Seeger, Michael (American Society for Microbiology, 1999)
Burkholderia sp. strain LB400 is one of the most potent aerobic polychlorobiphenyl (PCB)-degrading microorganisms that have been characterized. Its PCB-dioxygenating activity originates predominantly or exclusively from the biphenyl dioxygenase encoded by its bph gene cluster. Analysis of the dioxygenation products of several di- to pentachlorinated biphenyls formed by this enzyme revealed a complex dependence of the regiospecificity and the yield of dioxygenation on the substitution patterns of both the oxidized and the nonoxidized rings. No dioxygenolytic attack involving chlorinated meta or para carbons was observed. Therefore, the ability of the enzyme to hydroxylate chlorinated carbons appears to be limited to the ortho position. However, it is not limited to monochlorinated rings, as evidenced by dioxygenation of the 2,4-disubstituted ring at carbons 2 and 3. This site of attack is strikingly different from that of the 2,5-dichlorinated ring, which has been shown to be dihydroxylated at positions 3 and 4 (J. D. Haddock, J. R. Horton, and D. T. Gibson, J. Bacteriol. 177:20–26, 1995). These results demonstrate that a second substituent of ortho-chlorinated rings crucially influences the site of dioxygenation at this ring and thereby determines whether or not the initial chlorobiphenyl oxidation product is further metabolized through the bph-encoded pathway. The 2,4-dichlorinated ring can alternatively be attacked at carbons 5 and 6. The preferred site crucially depends on the substitution pattern of the other ring. The formation of more than a single dioxygenation product was found predominantly with congeners that contain two chlorinated rings, both of which are similarly prone to dioxygenation or one is substituted only at carbon 3.